Influences of nano-particles on dynamic strength of ultra-high performance concrete - Su, Y.; Li, Jun; Wu, C.; Wu, P.; Li, Z. (Elsevier, 2016)
© 2016 Elsevier Ltd. Known for its high strength, ductility and durability, ultra-high performance concrete (UHPC) is a topic of interest in recent years for scientists and civil engineers. Great potential application of UHPC has driven increasingly more investments and research into this industry. In recent studies, taken advantage of the nanotechnology, novel UHPC material with nano material addition was developed. Great static performance improvement was observed when compared with normal strength concrete. To obtain full understanding of material properties, especially dynamic performance, Split-Hopkinson Pressure Bar (SHPB) tests were conducted on this new concrete material. For comparison purpose, static properties from uniaxial compression and split tensile tests are obtained and discussed. In this paper, effects of nanomaterials on behaviour of UHPC are assessed through group comparison. Dynamic increase factor (DIF) values for both the dynamic compressive strength and tensile strength are generated. It is found that the strength of UHPC increases with the rising of strain rates and dosage of nano material influences UHPC dynamic properties. However, UHPC is noted to be less rate sensitive comparing with normal strength concrete. Microscopy analysis including Scanning Electron Microscope (SEM) Analysis, X-Ray Diffraction (XRD) Analysis and X-Ray Fluorescence (XRF) Analysis are conducted to understand the macroscopic failure phenomenon, element composition and concrete hydration process.